Laparoscopic, minilaparoscopic, single-port and percutaneous hysterectomy: Comparison of perioperative outcomes of minimally invasive approaches in gynecologic surgery. (September 2017) - Rossitto, C.; Cianci, S.; Gueli Alletti, S.; Perrone, E.; Pizzacalla, S.; Scambia, G.
Abstract: Objectives: During the last decade endoscopic surgical procedures have been constantly evolving. The latest innovation in ultra-minimally invasive surgery (MIS) is the percutaneous technology (Percuvance™ Percutaneous Surgical System (PSS), Teleflex Inc., USA). We compared surgical outcome of hysterectomy, in a retrospective cohort study using the most recent MIS techniques as single-site (LESS) surgery, 3 mm laparoscopy (MiniLPS) and percutaneous system (PSS) with standard laparoscopy (LPS). Study design: This is a matched retrospective cohort study. Endometrial Hyperplasia/Early stage endometrial cancer or benign pathology were the indication for surgery. Data of laparoscopic hysterectomies performed between May 2013 and April 2016 using PSS, LPS, MiniLPS, and LESS were collected and compared. Results: The characteristics of each group were similar. The median Operative time (OT) was significantly longer in LESS compared to all other groups (120 min [range 55–165] in LESS, 91 min [range 60–180] in MiniLPS, 70 min [range 55–230] in LPS and 65 [range 40–180] in PSS; p = 0.0001). No significant differences among the 4 groups were observed in terms of estimated blood loss, conversion to laparoscopy or laparotomy, and intra e post-operative complications. Statistically significant differences were recorded in median VAS 24 h (2 [range 0–3] in PSS, 2 [range 0–3] in MiniLPS, 3 [range 2–5] in LESS and 2 [range 1–5] in LPS; p = 0.0001). The average time of discharge was (1 day [range 1–3] in PSS, 1 day [range 1–2] in MiniLPS, 1 days [range 1–2] in LESS and 1 day [range 1–3] in LPS; p = 0.99). Conclusions: Data show that the effort to minimize the impact of surgical invasiveness can be feasible and could improve the advantages, not only in terms of aesthetic outcomes, even if the differences among the endoscopic approaches have not a relevant clinical impact. The technology innovations like PSS maintain the same triangulation between instruments as standard LPS with an evident decrease of the invasiveness thanks to reduced instruments size, even if the lack of suitability of bipolar energy, that require a multifunction instrument, remain a limit of these instruments.